Connecting to Compete 2014 : Trade Logistics in the Global Economy--The Logistics Performance Index and Its Indicators - Arvis, Jean-François; Saslavsky, Daniel; Ojala, Lauri; Shepherd, Ben; Busch, Christina; Raj, Anasuya (World Bank, Washington, DC, 2014)
Improving logistics performance is at the core of the economic growth and competitiveness agenda. Policymakers globally recognize the logistics sector as one of their key pillars for development. Trade powerhouses in Europe like the Netherlands or in developing countries like Vietnam or Indonesia see seamless and sustainable logistics as an engine of growth and of integration with global value chains. Indeed, inefficient logistics raises the costs of trading and reduces the potential for global integration. This is a hefty burden for developing countries trying to compete in the global marketplace. Since 2007, the Logistics Performance